Analysis of Ronald Coase’s theorem from the perspective of natural resources management - Śleszyński, Jerzy (Economics and Environment, 2024)
The aim of this article is to consider why the Coase theorem is used so rarely in the field of environmental protection policy and why possible proposals for the implementation of this solution are exposed to harsh criticism. Ronald Coase points out the significant problem of regulatory costs, and his proposal for negotiations may be a panacea for certain over-administration, excessive interventionism, regulatory rigidity or lack of trust in the market mechanism. However, according to the author of this paper, the implementation of the Coase theorem in the most typical and significant areas and problems of environmental policy is either not possible, will encounter enormous difficulties, or is questionable from the point of view of natural resources and social welfare. The reasons for the limitations will be discussed, including undefined or imprecisely defined ownership rights to many environmental resources, the non-market nature of many environmental goods depriving them of a market price, and above all, the chronic asymmetry of the parties that would negotiate with each other on an equal basis.